Evaluasi Kinerja Pegawai Jabatan Struktural dengan Jabatan Fungsional Pasca Terbit Kebijakan Tunjangan Tambahan Penghasilan di Dinas Pendidikan Kabupaten MAPPII - Komnas Minipko; Ferinandus Leonardo Snanfi; Sri Sediyaningsih (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to evaluate the performance of employees in structural positions with functional positions after the issuance of the additional income allowance policy at the Mappi district education office. The method used in this research is qualitative. Based on interview data, the research results show that 1).Quality of work. In particular, there is no difference in performance achievements pre and post TPP administration. 2.) Quantity of work. There are differences in the quantity of work pre and post TPP in structural positions and functional officials. For structural officials, work is assigned in a quantity of 12 points post-TPP from 10 points pre-TPP, this means that there is an additional workload after the TPP is implemented. Furthermore, for functional officials, there has been a change in the provision of TPP from 12 workload points during pre-TPP to 10 TPP weight points, meaning there is a decrease in workload. 3). Supervision of structural positions. The obstacle is in the form of a lack of readiness of officials due to changes in workload which has increased more than after the TPP was given, then another obstacle is that the TPP program is not attractive. 4.) Attendance. The TPP program provided is unable to increase employee motivation to improve their performance because the amount of TPP received refers to work performance achievements, not based on discipline or the level of attendance of officials. 5) Conservation. The provision of TPP has fulfilled the efficient elements. Keywords: performance evaluation, TPP policy, structural position employees, functional position employees.